Analisis Data Pola Musim di Indonesia Menggunakan Data Equivalent Water Height (EWH) dari Satelit GRACE - Muhammad Taufiq; Ira Mutiara Anjasmara (Yayasan Literasi Sains Indonesia, 2025)
Indonesia, as a tropical country, exhibits rainfall patterns that are strongly influenced by both global and regional atmospheric dynamics. The seasonal climate system in Indonesia, which consists of the wet season, dry season, and transitional periods, plays a crucial role in water resource management, agricultural activities, and disaster mitigation. To better understand these complex atmospheric and hydrological interactions, climatological parameters such as Equivalent Water Height (EWH) serve as important indicators of terrestrial water storage variability. The application of GRACE and GRACE-FO satellite missions provides a novel approach to monitoring hydrological dynamics through EWH, enabling large-scale and continuous observations of terrestrial water storage changes. The results of this study reveal a strong negative relationship between the Oceanic Niño Index (ONI) and EWH at zero time lag, indicating that El Niño events tend to reduce terrestrial water storage across Indonesia. This simultaneous response suggests that changes in atmospheric circulation during El Niño phases immediately affect hydrological conditions over land. In particular, the reduction in water storage is primarily associated with weakened moisture transport from both the Indian Ocean and the Pacific Ocean, which are the main sources of atmospheric water vapor influencing Indonesia’s climate system. As a result, decreased moisture convergence leads to reduced precipitation and a rapid decline in terrestrial water reserves. Bias evaluation further indicates distinct spatial patterns across the Indonesian region. Negative bias predominantly occurs in Sumatra and Kalimantan, whereas positive bias is more commonly observed in Nusa Tenggara and Maluku. In addition, the RMSE analysis shows that EWH estimates are relatively more accurate in regions with homogeneous rainfall patterns, while their performance decreases in areas characterized by high rainfall variability. These findings highlight the importance of considering regional climatic characteristics when interpreting satellite-based hydrological observations and emphasize the role of large-scale atmospheric–oceanic interactions in shaping terrestrial water storage dynamics in Indonesia.